The Influence of Marketing Mix on Purchase Intention at Argomulyo Culinary Center - Tirta, Adrianus; Pele Widjaja; Irma Subagio; Ryani Gunawan; Enrico Nirwan Histanto; Kevin Gunawan Halim (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
The Argomulyo Culinary Center (ACC), a growing culinary hub in Yogyakarta, aims to attract local tourists but lacks a structured marketing approach to increase visitor purchase intention. To establish a foundation for designing a marketing approach, this study examines the influence of the 4P Marketing Mix (Product, Price, Place, and Promotion) on Purchase Intention at ACC. A quantitative approach was used, employing Multiple Linear Regression with Purposive Sampling of 160 Yogyakarta-based visitors. Data were collected through structured surveys and analyzed using SPSS software. The results indicate that Product has a significant effect on Purchase Intention (β = 0.226, p = 0.013), while Price (p = 0.983), Place (p = 0.508), and Promotion (p = 0.227) do not have significant partial effects. However, all four variables simultaneously influence Purchase Intention (p < 0.001). These findings suggest that ACC should prioritize product development, including expanding menu variety, enhancing quality of ingredients, and improving food presentation. Additionally, a training program for tenants is recommended, focusing on culinary innovation, digital marketing, and customer experience enhancement. These efforts are expected to strengthen ACC’s competitive position and attract more visitors. This research offers valuable insights for culinary businesses, especially in developing economies, struggling to establish a strong market presence. It demonstrates the critical role of product quality and innovation in driving purchase intention, highlighting the need for a holistic marketing approach and targeted training programs to enhance competitiveness.